The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.6113/jpe.2016.16.1.329
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Voltage Control for Reactive Power Sharing in an Islanded Microgrid

Abstract: Owing to mismatched feeder impedances in an islanded microgrid, the conventional droop control method typically results in errors in reactive power sharing among distributed generation (DG) units. In this study, an improved droop control strategy based on secondary voltage control is proposed to enhance the reactive power sharing accuracy in an islanded microgrid. In a DG local controller, an integral term is introduced into the voltage droop function, in which the voltage compensation signal from the secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…An improved droop control scheme was proposed for reactive power sharing in islanded microgrids, which uses the error reduction operation by low-bandwidth synchronization signal and the voltage recovery operation to compensate the voltage reduction due to the error reduction operation [11,12]. A secondary voltage control scheme was proposed for reactive power sharing in islanded microgrid [24]. This scheme inserts an integral term into the voltage droop function in which the voltage compensation signal from the secondary voltage control is utilized as the reactive power reference.…”
Section: Droop Control Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved droop control scheme was proposed for reactive power sharing in islanded microgrids, which uses the error reduction operation by low-bandwidth synchronization signal and the voltage recovery operation to compensate the voltage reduction due to the error reduction operation [11,12]. A secondary voltage control scheme was proposed for reactive power sharing in islanded microgrid [24]. This scheme inserts an integral term into the voltage droop function in which the voltage compensation signal from the secondary voltage control is utilized as the reactive power reference.…”
Section: Droop Control Conceptmentioning
confidence: 99%
“…A secondary voltage control scheme was proposed for reactive power sharing in islanded microgrid [24]. This scheme inserts an integral term into the voltage droop function in which the voltage compensation signal from the secondary voltage control is utilized as the reactive power reference.…”
mentioning
confidence: 99%
“…The stability and dynamic performance of a system with the IM-P and IM-PQ methods are analyzed and compared with the small-signal state-space model following the modeling approach in [14], [28].…”
Section: B Dynamic and Stability Performancementioning
confidence: 99%
“…However, when considering the voltage deviations introduced by both the V-Q droop controller and the voltage drop on the equivalent impedance, the PCC voltage may be smaller than the minimum allowable value as illustrated in injected into the microgrid. Therefore, the droop controller should be improved to consider the PCC voltage deviation by using a second-level control scheme with communication [20]- [23] or the proposed communicationless method as elaborated in the next Section.…”
Section: B Pcc Voltage Deviation Under a Droop Control Scheme With Amentioning
confidence: 99%
“…Secondary frequency and voltage control via distributed averaging was proposed in [22], which uses localized information and nearest-neighbor communication to perform secondary control actions. An improved droop control strategy based on secondary voltage control was proposed in [23], where information on the voltage compensation signal is broadcasted from a central controller to each of the DG units. It has been demonstrated that the hierarchical control scheme can effectively restore the PCC voltage deviation.…”
Section: Introductionmentioning
confidence: 99%